The concept of genocide has evolved in international and domestic law - Issa, Prof. Dr. Hussein Abdali Issa (Sulaimani Journal for Humanities, 2024)
On December 9, 1948, the United Nations General Assembly adopted the Convention on the Prevention and Punishment of the Crime of Genocide. Despite the passage of more than seventy-six years, the definition of genocide in Article II remains unchanged. However, the practices of ad hoc international criminal tribunals have revealed problems in its application to the cases of genocide they have examined. Furthermore, the legislative formulation of this concept in the Rome Statute of the International Criminal Court of 1998, as well as in the penal codes of several States Parties to the Convention that criminalize genocide, differs from its definition in the international convention. This indicates a divergence in the understanding of the genocide definition in the 1948 Convention, both in international and domestic law, since its adoption. This necessitates a review of the Convention by amending Article II to reflect developments in this area. Therefore, this research aims to study the developments that have occurred in the concept of the crime of genocide during the period from the adoption of the Convention on the Prevention and Punishment of the Crime of Genocide of 1948 until now, based on a study of this international convention, the basic systems of the temporary international criminal tribunals and their applications, the Rome Statute of the International Criminal Court of 1998, as well as the penal legislation of a number of countries, in order to reach appropriate recommendations for developing an integrated concept of the crime of genocide, which has a great impact on addressing this grave international crime, protecting the human groups targeted by it, and preventing its perpetrators from escaping punishment.
Keywords: Genocide; International Convention 1948; International Criminal Tribunals; Penal Legislation